Examining navigators' job satisfaction in royal Malaysian air force through the lenses of Herzberg's motivation- hygiene theory - Mahzan, N. (2014)
Many studies investigate job satisfaction and motivation in the workplace using Herzberg's motivation-hygiene factor theory; however, no Ill' specifically relate these factors to Navigators in the Royal Malaysian Air Force in which limited promotion is available, This study investigated the factors affecting job satisfaction for navigators in the Royal Malaysian Air Force, 54 respondents from various operational squadrons and units completed the survey, The factors adapted from Herzberg's Motivation-Hygiene Theory were tested, The motivation factors achievement, recognition, growth, work itself and promotion were found to be significance and dominance in this study whereas policies, flight safety and relationship with leaders were the significant hygiene factors. A multiple regression is also conducted and from result found that career growth is the most significant factor that influence the job satisfaction of Navigators in the Royal Malaysian Air Force.